(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2019)
The Marcel Duchamp absolute gesture is such a gesture that inaugurates an escape movement from any Symbolic Order (another name of this movement is the Deleuzian «becoming-animal»); a gesture that, obviously, Duchamp does not stop play out, because each time he enacts it, this is a new gesture; there is no rule for the absolute gesture. In fact, if it existed it would not be absolute. Duchamp is such an ‘artist’ who is without work, then, because what matters is not art, but the making of one’s existence something unique. The absolute gesture consists in the making of art a form of life.